Cultural and Gender Dimensions of Safety: Enhancing Women’s Privacy and Equity in Iraqi Housing Design - Itma, Mohammed; Khaleefa, Taghreed (Journal of Architectural/Planning Research and Studies (JARS), 2025)
Sense of safety within residential environments is a multifaceted challenge, especially regarding gender cultural requirements. Do privacy specifications of housing affect women’s and men’s sense of safety similarly? This research delves into the most salient aspect of housing specifications, which is the relationship between the external and internal environment of residential units and its influence on women’s sense of safety in Iraq. The study conducted a comprehensive literature review and chose Koya City as a case study for analysis and engagement with relevant stakeholders. The complex interaction between indoor and outdoor spaces was explored to estimate their impact on women’s sense of safety compared to men. The study uses qualitative and quantitative methodologies to identify strategies and design interventions that might effectively mitigate safety concerns and promote inclusive and empowering living environments for women. The main conclusion of the study confirms that the relationship between the housing unit and the surrounding environment greatly affects women’s sense of privacy and safety, which shows the need to consider traditional concepts and norms to enhance this relationship and inform future low-rise, medium-density housing design.